2023
DOI: 10.1002/mnfr.202300137
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Free and Protein‐Bound Maillard Reaction Products N‐ε‐Carboxymethyllysine, N‐ε‐Fructosyllysine, and Pyrraline on Nrf2 and NFκB in HCT 116 Cells

Abstract: ScopeMaillard reaction products (MRPs) are believed to interact with the receptor for advanced glycation endproducts (RAGE) and lead to a pro‐inflammatory cellular response. The structural basis for this interaction is scarcely understood. This study investigates the effect of individual lysine modifications in free form or bound to casein on human colon cancer cells.Methods and resultsSelectively glycated casein containing either protein‐bound N‐ε‐carboxymethyllysine (CML), N‐ε‐fructosyllysine (FL), or pyrral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Additionally, although we chose the bioactive marker of AGEs, CML, to study its effects on gut microbiota and intestinal barrier, due to the complex variety and origin of AGEs, the specific active ingredients of AGEs might cause different biological effects. For example, Raupbach et al 65 found that free or protein-bound CML did not activate NFκB and Nrf2 in human colon cancer cells (HCT 116 cells), whereas casein-bound pyrraline activated Nrf2, and RAGE expression was not affected by free or casein-bound CML or pyrraline. However, Mastrocola et al 45 demonstrated that a diet enriched with MG-H1-modified casein (formed by mixing 10% solution of sodium caseinate with MGO and heating for 4 h) decreased SCFA-producing bacteria, increased RAGE expression in the ileum, and induced metabolic derangements.…”
Section: Free and Bound CML Treatments Promoted Age-receptor Expressionmentioning
confidence: 99%
“…Additionally, although we chose the bioactive marker of AGEs, CML, to study its effects on gut microbiota and intestinal barrier, due to the complex variety and origin of AGEs, the specific active ingredients of AGEs might cause different biological effects. For example, Raupbach et al 65 found that free or protein-bound CML did not activate NFκB and Nrf2 in human colon cancer cells (HCT 116 cells), whereas casein-bound pyrraline activated Nrf2, and RAGE expression was not affected by free or casein-bound CML or pyrraline. However, Mastrocola et al 45 demonstrated that a diet enriched with MG-H1-modified casein (formed by mixing 10% solution of sodium caseinate with MGO and heating for 4 h) decreased SCFA-producing bacteria, increased RAGE expression in the ileum, and induced metabolic derangements.…”
Section: Free and Bound CML Treatments Promoted Age-receptor Expressionmentioning
confidence: 99%